Biossorção do corante têxtil vermelho 4B utilizando resíduos agroindustriais após colonização fúngica - Crespão, Laianne Mayara Pezenti (2017)
The presence of dyes in water bodies, even at low concentrations, can cause serious problems in aquatic biota and human health. In this way, this work aims at the use of agroindustrial residues as adsorbent material, since this material is found in large quantities and at a lower cost than other adsorbents generally used, however, it is necessary to evaluate the interaction between the adsorbent material and the pollutant of Interest, as well as to verify the parameters that exert influence in this interaction. Therefore, this work evaluated the capacity of the sugarcane bagasse and pupunha palm heart, in the in natura forms and after fungal colonization, where the residues were used as substrate for the cultivation of the edible fungus Pleurotus ostreatus, in the Biosorption of the reactive dye Red 4B. The characterization of the materials was performed using MEV, FTIT, Boehm titration, Zero Load Point and Thermogravimetry. The biosorption assays evaluated the influence of pH, contact time, concentration and temperature, where pH 2.0 was obtained as the most favorable in all biosorbents tested. The contact time required for the system to equilibrate was 260 minutes for the biosorbents of cane in natura, colonized cane and in natura palmito, where only the colonized palmito required a time of 400 minutes. All biosorbents followed the kinetic model of Pseudo-Second Order. The experimental data obtained in the equilibrium test (influence of concentration) were adjusted to the Langmuir isothermal model for the biosorbents of Cana in natura and Freundlich for the colonized, with the maximum biosorption capacity (Qeqmax) found of 37.13 mg.g -1 and 10.63 mg.g-1 respectively. The palmito biosorbents presented Qeqmax of 6.98 and 10.68 for the in natura and colonized forms respectively, both of which were better adjusted to the Langmuir model, suggesting that the dye removal occurs in a monolayer on the surface of both biosorbents. It was also verified the influence of the temperature in the process, where for sugarcane, isothermal curves were constructed at 3 different temperatures, where it was observed that in higher concentrations, the increase of the temperature causes a decrease in the biosorption of the dye, Indicating that it is an exothermic process. The thermodynamic models applied to the inorganic and colonized palmito biosorbents indicated an endothermic process for both, with a small increase in biosorption capacity as a function of temperature increase, when the solution at the tested concentration (50.0 mg.g- 1). Finally, when testing the biosorbents in industrial effluent, all demonstrated good efficiency in the removal of the red dye 4B present in aqueous medium, following the same behavior obtained in the tests with synthetic solutions.